THE USE OF SOURCES IN TEACHING GRAMMAR FOR NON-LINGUISTIC FACULTIES (Лучшие интеллектуальные исследования, 2025)
Abstract: Teaching grammar in non-linguistic faculties presents unique challenges, as students often prioritize subject-specific knowledge over language proficiency. However, effective grammar instruction is crucial for developing clear communication, academic writing, and professional competency. This article explores strategies for teaching grammar to students in non-linguistic disciplines, emphasizing contextualized learning, practical applications, and integrative methodologies that align with their field-specific needs. The role of technology, task-based learning, interdisciplinary approaches, and renowned grammar resources in enhancing grammar instruction is also discussed.